Pengaruh Faktor-Faktor Makroekonomi Terhadap Harga Cryptocurrency: Analisis Multi-Koin (2016-2024) - Ammar, Muflih; Maya Sari; Netti Siska Nurhayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study analyzes the impact of inflation (Consumer Price Index/CPI) and interest rates (Federal Funds Rate) on the prices of five major cryptocurrencies—Bitcoin (BTC), Ethereum (ETH), Ripple (XRP), Dogecoin (DOGE), and Stellar (XLM)—over the period 2016–2024. Employing a quantitative approach, the study develops five separate multiple regression models, each representing one cryptocurrency as the dependent variable (Y). The results indicate that BTC, ETH, and DOGE are positively influenced by both inflation and interest rates. In contrast, XRP and XLM are only significantly and positively affected by inflation, while interest rates show no significant impact on their prices. The F-tests for each model confirm that inflation and interest rates simultaneously exert a significant effect on the prices of all five cryptocurrencies. These findings support the Arbitrage Pricing Theory (APT), which posits that asset valuation is determined by systematic risk factors, implying that even cryptocurrencies are not immune to the influence of inflation and interest rates.